Diskresi Presiden dalam Pengangkatan Menteri Negara: Analisis Konstitusional Batasan dan Pertanggungjawaban dalam Sistem Presidensial Indonesia: Presidential Discretion in the Appointment of State Ministers: A Constitutional Analysis of Limits and Accountability in Indonesia’s Presidential System - Listyani Effendi; Dewi Sulastri (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
This article discusses the discretionary authority of the President in the appointment and dismissal of ministers within Indonesia's presidential system of government. In this system, the President holds prerogative rights guaranteed by the Constitution, as stated in Article 17 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Although the President has considerable freedom, the use of such discretion is not absolute and must adhere to the principles of the rule of law, democracy, and good governance. Using a normative approach through library research, this article analyzes the constitutional foundation, limitations, and forms of accountability of presidential discretion in appointing ministers. It also evaluates President Prabowo Subianto’s cabinet reshuffle practices in response to political dynamics and public demands. The analysis shows that while ministerial appointments fall under the President's prerogative rights, their implementation must consider aspects of competence, integrity, and public accountability. Discretion should serve as a tool to enhance the effectiveness of governance, not as a means of exercising unchecked power. Therefore, transparency, professionalism, and accountability are fundamental principles in the exercise of executive discretion in Indonesia.